Toxin synergism in snake venoms. (1st October 2016) - Laustsen, Andreas Hougaard
Abstract: Synergism between venom toxins exists for a range of snake species. Synergism can be derived from both intermolecular interactions and supramolecular interactions between venom components, and can be the result of toxins targeting the same protein, biochemical pathway or physiological process. Few simple systematic tools and methods for determining the presence of synergism exist, but include co-administration of venom components and assessment of Accumulated Toxicity Scores. A better understanding of how to investigate synergism in snake venoms may help unravel strategies for developing novel therapies against snakebite envenoming by elucidating mechanisms for toxicity and interactions between venom components.